2019
DOI: 10.1186/s12889-019-7920-9
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to adopt wearable devices with behavioral and economic incentives by health insurance wellness programs: results of a US cross-sectional survey with multiple consumer health vignettes

Abstract: BackgroundThe number of health-related wearable devices is growing but it is not clear if Americans are willing to adopt health insurance wellness programs based on wearables and the incentives with which they would be more willing to adopt.MethodsIn this cross-sectional study we used a survey methodology, usage vignettes and a dichotomous scale to examine U.S. residents’ willingness to adopt wearables (WTAW) in six use-cases where it was mandatory to use a wearable device and share the resulting data with a h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The training approach with cases and curricular options we presented provides a source of options for clinicians, teachers, and program directors to help others develop knowledge, skills, and attitudes and has worked for other complex endeavors (e.g., culture and diversity, rural health) (Gifford et al 2012 ; Office of Rural Health and Department of Veterans Affairs Employee Education System 2017 ; Hilty et al 2018 ; Hilty et al 2018 ; Kurtz 2018 ). Methodologies are needed to develop, implement, and evaluate (quantitative, qualitative) clinically and competency-based interventions (Proctor et al 2010 ; Curran et al 2012 ; Gargon et al 2019 ; Marcolino et al 2019 ; Solino-Fernandez et al 2019 ). These learner-centered approaches parallel patient-centered ones and ensure quality care via technology (Hilty et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The training approach with cases and curricular options we presented provides a source of options for clinicians, teachers, and program directors to help others develop knowledge, skills, and attitudes and has worked for other complex endeavors (e.g., culture and diversity, rural health) (Gifford et al 2012 ; Office of Rural Health and Department of Veterans Affairs Employee Education System 2017 ; Hilty et al 2018 ; Hilty et al 2018 ; Kurtz 2018 ). Methodologies are needed to develop, implement, and evaluate (quantitative, qualitative) clinically and competency-based interventions (Proctor et al 2010 ; Curran et al 2012 ; Gargon et al 2019 ; Marcolino et al 2019 ; Solino-Fernandez et al 2019 ). These learner-centered approaches parallel patient-centered ones and ensure quality care via technology (Hilty et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This research suggests the influence of incentive programs on effective consumer adoption. Another study on wearable devices and insurance incentives found that Americans are willing to use wearable devices if there are health and/or economic motivations (Soliño-Fernandez et al, 2019). Some are calling for FDA regulation of health and wellness apps claiming that the lack of policy results in oversight by technology developers (Kasperbauer & Wright, 2020).…”
Section: Consumer and Policy Influencementioning
confidence: 99%
“…Workplace wellness programs play a vital role in supporting healthy choices and improving the quality of life of workers to benefit the employers in the long term. [ 34 ] Behavioral and economic incentives (such as fitness and yoga instruction, stress management classes, healthy food canteens, transit options, employee assistance programs, and worksite health clinics) have shown to boost the workforce morale. [ 34 ] In the case of injuries and accidents, employers may offer workers compensation benefits, temporary or permanent total disability benefits, social security disability insurance, and death benefits.…”
Section: Occupational Risks and Risk‐mitigating Interventionsmentioning
confidence: 99%
“…[ 34 ] Behavioral and economic incentives (such as fitness and yoga instruction, stress management classes, healthy food canteens, transit options, employee assistance programs, and worksite health clinics) have shown to boost the workforce morale. [ 34 ] In the case of injuries and accidents, employers may offer workers compensation benefits, temporary or permanent total disability benefits, social security disability insurance, and death benefits. To raise global awareness about the prevention of occupational injuries, accidents and diseases, the ILO World Day for Safety and Health is observed annually on April 28.…”
Section: Occupational Risks and Risk‐mitigating Interventionsmentioning
confidence: 99%